Existing treatment methods for the development of fetal growth retardation - Deinichenko, O. V.; Kyrychenko, M. M.; Kolokot, N. H.; Дейніченко, Олена Валеріївна; Кириченко, Михайло Михайлович; Колокот, Наталя Григорівна (Запорізький державний медико-фармацевтичний університет, 2024)
Diagnosis, treatment, and prevention of fetal growth retardation (FGR) is one of the urgent problems of modern obstetrics. According to various authors, the prevalence of this syndrome in various obstetric pathologies ranges from 11% to 36%. In recent years, the incidence of FGR syndrome has been increasing.
Keywords: тези доповідей